Chemical-Structural Identification of Crude Gelatin from Jellyfish (Stomolophus meleagris) and Evaluation of Its Potential Biological Activity - Dania Marisol Esparza-Espinoza; Hisila del Carmen Santacruz-Ortega; Maribel Plascencia-Jatomea; Santiago P. Aubourg; Jesús Aarón Salazar-Leyva; Francisco Rodríguez-Felix; Josafat Marina Ezquerra-Brauer (Fishes, 2023)
The demand for jellyfish is growing worldwide, especially due to their high nutraceutical value. In this study, the extraction and characterization of crude gelatin from the brown cannonball jellyfish (Stomolophus meleagris), which is periodically found in large volumes on the American Pacific coasts, were carried out. The crude gelatin obtained by alkaline treatment, with subsequent heat and dialysis treatment, showed an ability to quench free radicals (via ABTS and ORAC methods), and protect human cells against oxidative damage (through inhibition of hemolysis by AAPH), and they protected against mutations caused by aflatoxin B1 in the Salmonella enterica Typhimurium TA100 strain. Furthermore, it was established that these extracts were innocuous for eukaryotic cells (genotoxicity assay). The amino acid profiles indicate a high concentration of glycine and proline, as well as charged amino acids. Electrophoretic, FT-IR, and 1H-NMR studies indicated that one of the main proteins present in this crude gelatin is collagen. The presence of collagen and other proteins was identified by proteomic studies. Alkaline crude gelatin from brown jellyfish could be considered as potential candidates to be evaluated as antioxidant agents in foods in future research.